Photooxidation of Toluene: Correlation of Noble Metal Loading on Titania and Activation Energy. (30th November 2016) - ur Rashid, Haroon; Sadiq, Mohammad; Abid Zia, Muhammad; Sadiq, Saima; Sohail Ahmad, M.; Aman, Razia; Humayun, Muhammad; Ali, Rahmat
Abstract : A series of platinum and palladium supported on titania catalysts were prepared by wet impregnation method with the Pt or Pd loading varying in the range of 0.1–1.2 weight percent. The catalysts were characterized by SEM, EDX, XRF, XRD, FT-IR, and BET surface area analysis. The catalysts were tested for their efficiency in the liquid phase solvent-free photooxidation of toluene to benzyl alcohol and benzaldehyde in the presence of molecular oxygen. The effect of noble metal contents on the activation energy was studied. Activation energy was found to be in a reciprocal relation to the platinum or palladium content of the catalyst. The percent conversion of toluene was observed to increase in response to an increase in the metal loading on titania. The apparent quantum yield, however, was independent of the platinum or palladium content of the catalyst.